2019
DOI: 10.1016/j.dcn.2019.100670
|View full text |Cite|
|
Sign up to set email alerts
|

Neural dynamics underlying coherent motion perception in children and adults

Abstract: Highlights We measured evoked responses to directional motion in children and adults. Two reliable components with distinct time-courses and topographies were identified. Both component waveforms exhibited clear age-related differences. Both early sensory and later decisional processes seem to develop across childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“… Nickl-Jockschat et al (2014) further showed in their activation likelihood estimation meta-analysis that structural deficits of MT were unique to the right hemisphere portion of the area MT in addition to hypoactivation of the left fusiform gyrus during face processing. In terms of motion and M pathway processing, as discussed above, it appears that maturation occurs at ages around 10 years ( Crewther et al, 1999 ; Langrova et al, 2006 ; Manning et al, 2019 ). Thus, we are suggesting that maturation in the case of high autistic tendency leaves a higher remnant PIm → MT projection in the mature visual system.…”
Section: Update - Abnormal Dorsal Stream Development and Connectivity In Autismmentioning
confidence: 98%
See 1 more Smart Citation
“… Nickl-Jockschat et al (2014) further showed in their activation likelihood estimation meta-analysis that structural deficits of MT were unique to the right hemisphere portion of the area MT in addition to hypoactivation of the left fusiform gyrus during face processing. In terms of motion and M pathway processing, as discussed above, it appears that maturation occurs at ages around 10 years ( Crewther et al, 1999 ; Langrova et al, 2006 ; Manning et al, 2019 ). Thus, we are suggesting that maturation in the case of high autistic tendency leaves a higher remnant PIm → MT projection in the mature visual system.…”
Section: Update - Abnormal Dorsal Stream Development and Connectivity In Autismmentioning
confidence: 98%
“… Langrova et al (2006) showed the presence of an early positivity in the motion onset VEP at a latency of around 200 ms that was clearly present in a group of 6–7 years children, still discernible at age 12, but had vanished beyond about 16 year age. More recently, Manning et al (2019) showed, using high density EEG recordings of onset to coherent dot motion in neurotypical development from 6 year to adult, that the younger children showed an extra contribution over lateral occipital cortex that was no longer present by ages 10–12 year.…”
Section: Updating Primate Developmental Visual Neurosciencementioning
confidence: 99%
“…During visual processing, EEG activity is dominated by N2, an ERP component related to visual motion perception. N2 is a negative-going deflection typically observed in posterior occipital and parietal areas, and responds to changes in visual motion (Luck 2014). Previous studies found N2 around 130-150 ms after stimulus onset in adults (Probst et al 1993;Kremláček et al 2004), and after around 180-220 ms in infants aged 8 months (Van der Meer et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…When we walk backward, on the other hand, the same point will contract and the flow will radiate toward the point (Bruce et al 2003 ). If our speed increases, the velocity in the optic flow will change accordingly, leading to changes in brain activity (Vilhelmsen et al 2015 ) that show a gradual developmental progression through childhood (Manning et al 2019 ). Thus, we rely on optic flow every time we move (Warren et al 2001 ), and it is a crucial source of information to control our walking direction and speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation